Hubungan Karakteristik dan Kepribadian Anak dengan Kejadian Bullying pada Siswa Kelas V di SD “X” di Kabupaten Badung - Ni Kadek Diyantini; Ni Luh Putu Eva Yanti; Sagung Mirah Lismawati (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
The phenomenon of bullying in children most often occurred in schools, especially primary schools. The final stages of school age (10-12 years) are very vulnerable involved in bullying. Many factors affect bullying in children, both internal and external of children. This study aims to determine the relationship between child’s characteristics and personalities with bullying in fifth grade students in the elementary school